Maternal exposure to farming environment protects offspring against allergic diseases by modulating the neonatal TLR‐Tregs‐Th axis. Issue 1 (17th August 2018) - Yu, Jinyan; Liu, Xiaoqiu; Li, Yanlei; Meng, Shanshan; Wu, Fei; Yan, Bingdi; Xue, Yanjun; Ma, Tiangang; Yang, Junling; Liu, Jing
Abstract: Background: As the development of urbanization in China, the morbidity of allergic disease rise up prominently even in children, which may be partially associated with the excessively clean environment. It has been reported that common microorganism in rural environment shows protective effects on allergic disease by modulating TLRs‐Tregs/Th cell axis. But the mechanism of this protection still needs to be elucidated in detail. We investigated the effects of maternal exposure to farming environment on the neonatal innate immune system, especially on the TLR‐Treg‐Th (Th1, Th2, Th9, and Th17) axis, in the Jilin province of China. Methods: Eighty‐four non‐farming and 42 farming pregnant women were recruited. Endotoxins and glucans in dust from the living rooms of the pregnant mothers were measured. Cord blood mononuclear cells were challenged with phytohemagglutinin, lipopolysaccharide, or peptidoglycan. Proliferative response of lymphocyte was measured by 3H‐TdR incorporation methods, CD4 + CD25 + FOXP3 + T cells percentage was assessed with flow cytometry, Tregs specific genes (FOXP3, LAG3, GITR, CTLA‐4 and TGF‐β) and TLR2, TLR4 genes expression were detected by RT‐PCR, specific cytokines of Th1, Th2, Th9, Th17 and Tregs were measured with flow cytometer, suppressive capacity of Tregs was tested by culturing with effector cells in vitro, and TLR2/4 gene polymorphism was detected. Results: Higher endotoxin content was observed in the living rooms of the farming mothers. Compared with that in the non‐farming group, in farming neonatal CBMCs, lymphocyte proliferation declined; the IFN‐γ/IL‐13 ratio increased; and the quantity of Tregs and gene expression of FOXP3, GITR, CTLA4 and TLR2 increased significantly (P < 0.05). Isolated Tregs suppressed the proliferation of effector T cells and IL‐13 production more strongly in vitro (P = 0.04, 0.03, respectively), and the TLR2 polymorphism affected FOXP3 expression and IFN‐γ and IL‐13 production. Conclusions: Maternal exposure to farming affected the quantity and function of neonatal Tregs upon stimulation with PPG and LPS, which partly contributed to reducing the risk for allergic diseases in the offspring. The results of our study will lay the theoretical foundation for allergic disease prevention in early life.